Evolução da gestão nas micro e pequenas empresas de turismo em Aracaju : 2012 a 2014 - Faria, Bianca Esperidião de (2015)
Micro and small companies, together with the individual companies, representing approximately 99% of formal enterprises in Brazil and account for 52% of jobs created with a formal contract. In addition, they account for approximately 27% of national GDP. However, despite the importance of SMEs, the observed mortality rate revolves around 27%. Or approximately 1/3 of the open MEPs close the doors before completing two years of operation. The main problems are related to failures in the management process. The tourism industry, which has grown in recent years, is part of that context and was the focus of this work. The main objective is to present developments in the management of business into three segments, namely: hosting Media, Bars and Restaurants, and Travel Agencies, making a comparison between 2012-2014. To that end, it adopted the criteria Excellence Model Management in Management methodology developed by the National Quality Foundation. On the results presented, we realize that there is potential in the analyzed companies, although there is a discontinuity in good management practices for the absence of a system vision of the entrepreneur.